EGFR Targeted Paclitaxel and Piperine Co-loaded Liposomes for the Treatment of Triple Negative Breast Cancer - Burande A.S.; Viswanadh M.K.; Jha A.; Mehata A.K.; Shaik A.; Agrawal N.; Poddar S.; Mahto S.K.; Muthu M.S. (My University, 2025)
Triple-negative breast (TNBC) cancer that is upregulated with epidermal growth factor receptor (EGFR), and devoid of both the hormonal receptors and epidermal growth factor receptor 2 (HER 2), has led to a concept of treating TNBC with EGFR-targeted therapeutics. The combination of paclitaxel (PTX) and piperine (PIP) may improve the bioavailability of paclitaxel for cancer therapy. TPGS (vit E-PEG 1000-succinate)-coated liposomes were prepared with PTX alone or in combination with PIP, and either with (targeted) or without (non-targeted) cetuximab (CTX) conjugation. The Bradford assay indicated that 75% of CTX has been conjugated on the liposomes. The size and percent encapsulation of PTX&PIP co-loaded liposomes were found to be in the range of 204 to 218 nm and 31–73%, respectively. The drug release rate was found to be higher at pH 5.5 in comparison with release at pH 6.4 and pH 7.4. Cellular uptake and toxicity studies on MDA-MB-231 cells showed that PTX&PIP co-loaded targeted liposomes have demonstrated superior uptake and cytotoxicity than their non-targeted counterparts. The IC50 values of both of the liposomal formulations were found to be significantly higher than PTX control. Indeed, combining PIP with PTX control has improved the cytotoxicity of PTX control, which proved the synergistic anticancer effect of PIP. Lyophilized liposomes showed an excellent stability profile with the size range between 189 and 210 nm. Plasma stability study revealed a slight increase in the particle size due to the adsorption of plasma proteins on the surface of liposomes. The long-term stability study also indicated that liposomes were stable at 4°C. © 2020, American Association of Pharmaceutical Scientists.